"I don't mean to be rude, but could you put a mask on while I'm here?" A qualitative study of risks experienced by domiciliary care workers in Wales during the COVID‐19 pandemic. (24th November 2022) - Prout, Hayley; Lugg‐Widger, Fiona V.; Brookes‐Howell, Lucy; Cannings‐John, Rebecca; Akbari, Ashley; John, Ann; Thomas, Daniel Rh.; Robling, Michael
Abstract: Domiciliary care workers (DCWs) continued to provide care to adults in their own homes throughout the COVID‐19 pandemic. The evidence of the impact of COVID‐19 on health outcomes of DCWs is currently mixed. The OSCAR study will quantify the impact of COVID‐19 upon health outcomes of DCWs in Wales, explore causes of variation and extrapolate to the rest of the UK DCW population. An embedded qualitative study aimed to explore DCW experiences during the pandemic, including factors that may have varied risk of exposure to COVID‐19 and adverse health and wellbeing outcomes. Registered DCWs working throughout Wales were invited to participate in a semi‐structured telephone interview. 24 DCWs were interviewed between February and July 2021. Themes were identified through inductive analysis using thematic coding. Several themes emerged relating to risk of exposure to COVID‐19. First, general changes to the role of the DCW during the pandemic were identified. Second, practical challenges for DCWs in the workplace were reported, including staff shortages, clients and families not following safety procedures, initial shortages of personal protective equipment (PPE), DCW criticism of standard use PPE, client difficulty with PPE and management of rapid antigen testing. Third, lack of government/employer preparation for a pandemic was described, including the reorganisation of staff clients and services, inadequate or confusing information for many DCWs, COVID‐19 training and the need for improved practical instruction and limited official standard risk assessments for DCWs. Pressure to attend work and perceptions of COVID‐19 risk and vaccination was also reported. In summary, this paper describes the risk factors associated with working during the pandemic. We have mapped recommendations for each problem using these qualitative findings including tailored training and better support for isolated team members and identified the required changes at several socio‐ecological levels.